Efektifitas Token Ekonomi untuk Meningkatkan Kemampuan Membaca pada Anak - Rizkitara, Rinanti Dwi (YASIN, 2024)
Reading skills play a vital role in everyone’s life. By ages 5-6, children should ideally begin recognizing early writing indicators, having already started learning grammar and developing a vocabulary of around 3,000 words. The aim of this study is to examine the effectiveness of a token economy system in enhancing children’s reading skills. This research is quantitative, employing an experimental approach. The intervention method used here is the token economy system, in which researchers apply an observation guide to monitor and adjust subjects’ behaviors to align with desired reading behaviors. The findings from this intervention show a rapid improvement in the subject's early reading skills. The child was able to identify and point to letters independently, differentiate between letters on their own, name words in pictures, and break down words independently. This study concludes that the token economy system is effective in improving children’s reading skills.